Optimization of the Financial Services Authority (OJK) as a Regulator and Supervisor of Insurance Related to the Issuance of Shipping Insurance Policy Guarantee Regulations to Support Indonesia's Economic Development - Marihot Simanjuntak (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the function of the Financial Services Authority in guiding and supervising insurance companies related to shipping insurance in the insurance legal system in Indonesia, and the effectiveness of the contribution of the Financial Services Authority in contributing to economic development in Indonesia. This research is normative juridical research with a focus on analyzing relevant laws and regulations. The approach includes a statutory approach, a conceptual approach, and a case approach to explain and solve problems. Data is obtained from library research and interviews. The results of this study show that: 1) Friedman's theory identifies OJK's imbalance in insurance law enforcement, prioritizing market players over large entities, with inconsistent policies and suboptimal consumer protection; 2) Raharjo's analysis underscores the necessity of a shipping insurance policy guarantee law to bolster OJK's role. Rawls' theory emphasizes the ignorance of justice. Troubled insurance cases emphasize the need for policy guarantees to alleviate consumer burden and attract investment, though OJK's operational costs from the state budget may tighten supervision. The research conclusion shows the importance of OJK's function for consumers, prompting the need for a shipping insurance policy guarantee law. FSAs in the US, Japan, and Singapore use state budget funds to supervise financial services, with success in all three countries.